Struktur Dan Komposisi Vegetasi Agroforest Pala (Myristica fragrans) di Kecamatan Sumberejo Kabupaten Tanggamus Lampung - Eni Widayanti; Afif Bintoro; Duryat Duryat (Jurnal Silva Tropika, 2020)
Agroforestry system is an optimal and sustainable land use system by combining forestry plants and agricultural crops on the same land management unit. Agroforestry consists of simple agroforestry and complex agroforestry (agroforest). Agroforest in Sumberejo subdistrict Tanggamus district cultivate certain types of plants, especially nutmeg. Nutmeg plants combined with agricultural crops and other forestry plants. Therefore, it is necessary to conduct research aimed at: 1) know the types of plants that make up the nutmeg agroforest vegetation; 2) determine the density of each type of plant composing the nutmeg agroforest vegetation; 3) know the structure of nutmeg agroforest in the Sumberejo district of Tanggamus. The study was conducted in Sumberejo of Tanggamus Lampung in Februari – March 2019. Sampling plot was done by census of the entire farmer population. The population consists of farmers who have their own community forest land with a minimum area of 0,25 ha. Data collection method was done by double plot method. The results showed that the nutmeg agroforestry constituent plants in Sumberejo of Tanggamus regency consisted of 42 species of plants that were included in 35 families. Nutmeg density of the tree phase reaches 60,5 individuals/ha. The structure was formed of 3 stratifications, they are strata C, D, and E.